Near-infrared emission of Nd-PSS films - Silva,Marcelo C. (2006)
We report a study of a new chemical synthetic route of polystyrene sulphonate (PSS) films doped with neodymium ion (Nd+3) from a neodymium nitrate solution. The UV-Vis-NIR spectrum presents an intense characteristic electronic transition at 800 nm and the infrared spectrum presents low definition bands as a result of Nd3+ coordination with PSS molecule. Additionally, the spectrum of Nd-PSS film presents the same line shape profile of Nd3+ salt in aqueous solution. Selective luminescence spectroscopy measures shows that the incorporation of neodymium ion introduces a red shift bands and a better line shape definition in UV luminescence compared to PSS film, decreasing the interaction between PSS aromatic groups. The near-infrared emission was observed in the large spectrum region from 600 to 800 nm; it is associated with the Nd3+ complex of PSS monomer.